2007
DOI: 10.1111/j.1444-0938.2006.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal colour vision is a handicap to playing cricket but not an insurmountable one

Abstract: Background:  Two studies have reported that abnormal colour vision is under‐represented among cricketers, presumably because cricketers with abnormal colour vision have difficulty seeing the red ball against the green grass of the cricket field and the green foliage around it. We have previously reported on the difficulties of five cricketers with abnormal colour vision but we have also reported that one of Australia’s finest cricketers was a protanope. This survey was undertaken to confirm the under‐represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…Thus, overall, 4.7% of our males had red/green colour deficiency compared to an expected 8% in European Caucasian males [ 56 ], who comprised the overwhelming majority of our males. This discrepancy may be due to our modest sample size, but it is consistent with findings that colour vision deficits are under-represented in high-level cricketers in England [ 57 ] and with another study [ 58 ] in which fewer first-grade cricketers than expected were found to be colour-vision deficient. None of the female cricketers were found to be colour deficient, and this is consistent with the much lower prevalence of red/green deficiency expected in females compared to males [ 56 ].…”
Section: Resultssupporting
confidence: 88%
“…Thus, overall, 4.7% of our males had red/green colour deficiency compared to an expected 8% in European Caucasian males [ 56 ], who comprised the overwhelming majority of our males. This discrepancy may be due to our modest sample size, but it is consistent with findings that colour vision deficits are under-represented in high-level cricketers in England [ 57 ] and with another study [ 58 ] in which fewer first-grade cricketers than expected were found to be colour-vision deficient. None of the female cricketers were found to be colour deficient, and this is consistent with the much lower prevalence of red/green deficiency expected in females compared to males [ 56 ].…”
Section: Resultssupporting
confidence: 88%
“…7,29 Three participants in this study self-reported a colour vision deficiency, which is relatively fewer than what would have been expected on the basis of frequency in the male population (about 8% of males). Either some players remain unaware of their colour vision deficiency, or rather that our results are consistent with others who have found an underrepresentation of individuals with a colour vision deficiency in first-class cricket 30 , further supporting the idea that a colour vision deficiency may present a potential barrier to optimal performance in cricket.…”
Section: Discussionsupporting
confidence: 89%
“…A significant proportion of individuals with a congenital colour vision deficiency have reported difficulties with ‘everyday tasks’ requiring colour vision, such as in recognising colours in sport or the television . First grade cricket has a lower representation of individuals with colour vision deficiencies; however, their performance was found to be similar to that of cricketers with normal colour vision . It was thought that there was an element of self‐selection of cricketers with congenital colour vision deficiency that could adequately compensate .…”
Section: Resultsmentioning
confidence: 99%